Multicentre Comparison of the Toxicity and Effectiveness of Lobaplatin-Based Versus Cisplatin-Based Adjuvant Chemotherapy in Oesophageal Carcinoma - Zheng, Yan; Li, Yin; Liu, Xianben; Sun, Haibo; Liang, Guanghui; Hu, Jiajia; Li, Liping; Xing, Wenqun (Frontiers in Oncology, 2021)
Objectives Lobaplatin (LBP), a third-generation cisplatin derivative has shown promising activity and few side effects in oesophageal squamous cell carcinoma (ESCC) in previous reports. We compared LBP plus docetaxel with cisplatin plus docetaxel as adjuvant chemotherapy in ESCC patients to determine the effects on overall survival (OS) and toxicity. Methods A multicentre retrospective study was performed using propensity score matching (PSM) with the Medicine-LinkDoc database. Patients diagnosed with stage II-III ESCC treated with adjuvant chemotherapy (cisplatin plus docetaxel or LBP plus docetaxel) between January 2013 and December 2016 were selected from 6 centres in China. Results There were 733 eligible ESCC patients. After PSM (1:1 ratio), 458 patients remained. The 5-year OS rates of the cisplatin and LBP groups were 25.9% and 23.6%, respectively (P=0.457). Leukopenia (grade III-IV/I-II/0: 2.62%/34.5%/59.39% versus 5.24%/43.23%/45.85%; P=0.0176), neutropenia (grade III-IV/I-II/0: 6.55%/37.56%/51.09% versus 4.37%/53.28%/36.34%; P=0.0015), nephrotoxicity (grade I-II/0: 13.97%/76.86% versus 26.64%/65.94%; P<0.001) and gastrointestinal symptoms (grade III-IV/I-II/0: 2.18%/54.59%/32.31% versus 6.55%/65.07%/20.88%; P=0.0011) were more frequent in the cisplatin group. Conclusions Compared with cisplatin plus docetaxel, LBP plus docetaxel provided the same survival benefits but lower side effects of myelosuppression and gastrointestinal symptoms. LBP plus docetaxel might be a choice for adjuvant chemotherapy in ESCC. Clinical Trial Registration Lobaplatin or Cisplatin in Adjuvant Chemotherapy for Oesophageal Carcinoma, identifier NCT03413436.